PROBLEMATIKA REGENERASI PENENUN SONGKET DI DESA MUARA PENIMBUNG ULU - Masyiroh, Uchie; Ardi Saputra; Aswasulasikin; Shomedran (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the problems of songket weaver regeneration in Muara Penimbung Ulu Village, Indralaya District, Ogan Ilir Regency. Regeneration is important in maintaining the sustainability of weaving skills as part of preserving local culture, but the involvement of the younger generation is still low. This study used a descriptive qualitative method with a purposive sampling technique involving 8 informants. Data were collected through interviews, observations, and documentation, then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the regeneration of songket weavers faces social, economic, and policy barriers. Social barriers include low interest from the younger generation and low environmental support. Economic barriers are related to low income and the attractiveness of weaving. Policy barriers are evident in the limitations and suboptimal implementation of programs. Government efforts through training have been carried out, but participation from the younger generation is still limited. The conclusion of this study indicates that the regeneration process of songket weavers has not been running optimally. Synergy is needed between the government, the community, and educational institutions to increase interest from the younger generation and strengthen the sustainability of weaving culture.